Education On The Importance Of Exclusive Breastfeeding For Pregnant And Breastfeeding Women In Hamlet I, E Village, Wonokerto, Tugumulyo District, Musi Rawas Regency, 2025 - Rita Susanti; Titin, Titin; Yulianti, Yulianti; Sari, Liya Lugita (Jurnal Inovasi Kerja Nyata, 2025)
Exclusive breastfeeding is the provision of breast milk as early as possible after delivery, given without a schedule and no other food, even water, until the baby is 6 months old. Exclusive breastfeeding is an ideal source of nutrition because its composition is naturally balanced and in accordance with the growth and development of the baby, so that exclusive breastfeeding is the most perfect food for babies in terms of quality and quantity, in addition to being cheap, easy to obtain and can also be given at any time of the day, the best and most perfect first food for babies. The purpose of this community service activity is to increase the knowledge and understanding of mothers about the importance of providing exclusive breastfeeding to babies and teach the correct breastfeeding techniques. This activity is carried out by providing counseling with leaflets to pregnant and breastfeeding mothers about breast milk and its benefits for the growth and development of babies. This counseling was carried out on June 9, 2025 in Dusun I, E. Wonokerto Village, Musi Rawas Regency, which was attended by 8 pregnant and breastfeeding participants. As a result, after the counseling, 8 pregnant and breastfeeding participants experienced an increase in knowledge about exclusive breastfeeding and the correct way to breastfeed. It is hoped that after this activity, all pregnant women and mothers who have babies aged 0-6 months can provide exclusive breastfeeding until the baby is 2 years old because breast milk contains nutrients and various immune substances that babies need so that it can protect babies from diseases such as diarrhea, earache, respiratory tract infections and allergies.